Quiet riots: race and poverty in the United States; the Kerner Report 20 years later - Harris, Fred R. (Pantheon Books [u.a.], 1988)
The 1967 riots and the Kerner Commission / Fred R. Harris -- The Kerner Report / John Herbers -- Poverty is still with us--and worse / David Hamilton -- Blacks, Hispanics, American Indians, and poverty--and what worked / Gary D. Sandefur -- The persistence of urban poverty / Terry K. Adams, Greg J. Duncan, and Willard L. Rodgers -- Separate societies / Gary Orfield -- The ghetto underclass and the changing structure of urban poverty / William Julius Wilson ... [et al.] -- Thomas Jefferson, the Kerner Commission, and the Retreat of Folly / Lynn A. Curtis -- Race and poverty in the United States--and what should be done / 1988 Commission on the Cities